2002
DOI: 10.1067/mtc.2002.123813
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive management of lung donors classified as unacceptable: Excellent recipient survival one year after transplantation

Abstract: Aggressive organ procurement organization management of donors initially considered unacceptable may increase the number of lungs available for transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(65 citation statements)
references
References 14 publications
1
61
0
2
Order By: Relevance
“…Frequently, what seems to be a marginal donor can be made quite acceptable [21]. Although a significant smoking history (o30 pack-yrs) in the donor is concerning, it is not an absolute contraindication to the use of otherwise suitable donor lungs.…”
Section: Current Availability Of Donor Lungsmentioning
confidence: 99%
“…Frequently, what seems to be a marginal donor can be made quite acceptable [21]. Although a significant smoking history (o30 pack-yrs) in the donor is concerning, it is not an absolute contraindication to the use of otherwise suitable donor lungs.…”
Section: Current Availability Of Donor Lungsmentioning
confidence: 99%
“…Oxygenation has been one criterion with which clinicians have rarely compromised. However, STRAZNICKA et al [51] and GABBAY et al [44] have shown that donors with poor initial oxygenation can be improved with aggressive management, and eventually used for LTx without significant impact on the postoperative course and 1-yr survival. Hence, donors with poor oxygenation should not be deemed unsuitable for transplantation, since up to 35% of them can be improved to reach an arterial oxygen tension (Pa,O 2 )/FI,O 2 ratio of w39.9 kPa (300 mmHg) after aggressive resuscitation.…”
Section: Extension Of Lung Donor Selection Criteriamentioning
confidence: 99%
“…However, the lungs are susceptible to interstitial oedema particularly in the context of brainstem death and many feel these changes are reversible, making the underlying lung suitable for transplantation. Straznicka et al 56 described the management of 27 unacceptable donors with a mean PaO 2 :FiO 2 of 13.7 kPa at initial assessment. All were treated with invasive monitoring, methylprednisolone, fluid restriction, inotropic agents, bronchoscopy and diuresis.…”
Section: Aggressive Medical Management Of Donormentioning
confidence: 99%